A genome-wide association study shows that common alleles of SMAD7 influence colorectal cancer risk. - Broderick, P; Carvajal-Carmona, L; Pittman, A; Webb, E; Howarth, K; Rowan, A; Lubbe, S; Spain, S; Sullivan, K; Fielding, S; Jaeger, E; Vijayakrishnan, J; et al. (2007)
To identify risk variants for colorectal cancer (CRC), we conducted a genome-wide association study, genotyping 550,163 tag SNPs in 940 individuals with familial colorectal tumor (627 CRC, 313 advanced adenomas) and 965 controls. We evaluated selected SNPs in three replication sample sets (7,473 cases, 5,984 controls) and identified three SNPs in SMAD7 (involved in TGF-beta and Wnt signaling) associated with CRC. Across the four sample sets, the association between rs4939827 and CRC was highly statistically significant (P(trend) = 1.0 x 10(-12)).